Dietary adaptation for weight loss maintenance at Yale (DAWLY): Protocol and predictions for a randomized controlled trial - Fang, Xi; Davis, Xue; Flack, Kyle D.; Duncan, Chavonn; Li, Fangyong; White, Marney; Grilo, Carlos; Small, Dana M. (Frontiers in Nutrition, 2022)
Background: Current therapies for obesity treatment are effective at producing short-term weight loss, but weight loss maintenance remains a significant challenge. Here we investigate the impact of pre-intervention diet on the efficacy of a dietary supplement to support weight loss maintenance. Preclinical work demonstrates that a vagal afferent pathway critical for sensing dietary lipids is blunted by a high-fat diet (HFD), resulting in a reduced preference for a low-fat emulsion and severe blunting of dopamine (DA) response to the gastric infusion of lipids. Infusion of the gut lipid messenger oleoylethanolamide (OEA), which is also depleted by HFD, immediately reverses this DA blunting and restores preference for the low-fat emulsion. Studies of OEA supplementation for weight loss in humans have had limited success. Given the strong effect of HFD on this pathway, we designed a study to test whether efficacy of OEA as a weight loss treatment is related to HFD. Methods/design: We employed a randomized, double-blind, placebo-controlled trial in which 100 adults with overweight/obesity (OW/OB) were randomized to receive either OEA or placebo once daily for 16 months. Following baseline evaluation of diet, metabolic health, adiposity, and brain response to a palatable an energy dense food, participants in both groups underwent a 4-month behavioral weight loss intervention (LEARN®) followed by a one-year maintenance period. The study aims are to 1) determine if dietary fat intake moderates the ability of OEA to improve weight loss and weight loss maintenance after a gold standard behavioral weight loss treatment; (2) identify biomarkers that predict outcome and optimize a stratification strategy; and (3) test a model underlying OEA’s effectiveness. Discussion: Focusing on interventions that target the gut-brain axis is supported by mounting evidence for the role of gut-brain signaling in food choice and modulation of this circuit by diet. This work has the potential to identify a novel gut-brain target for weight loss maintenance and support a precision medicine approach to behavioral weight loss plus supplementation that is easy and inexpensive to implement.